Contextual Interference in Movements of the Same Class: Differential Effects on Program and Parameter Learning - Wulf, Gabriele; Lee, Timothy D. (Journal of motor behavior, 1993)
Contextual interference effects in motor learning usually were not found when the tasks to be learned presumably required the same generalized motor program (GMP) and differed only with regard to the movement parameters (see Lee, Wulf, & Schmidt, 1992; Magill & Hall, 1990). Thus, tasks requiring different motor programs (e.g., different relative timings) seemed to be a prerequisite for random practice to be more effective than blocked practice. However, the previous studies (that did not find random/blocked differences) used global error measures that confounded errors in relative timing and errors in absolute timing. In the present study, subjects practiced three movement patterns that had the same relative timing (requiring the same GMP) but different overall durations (requiring different parameters). Errors in relative timing and in absolute timing were assessed separately. The results indicate that random practice is more effective for the learning of relative timing (GMP learning) and less effective for the learning of absolute timing (parameter learning) than blocked practice. Preliminary ideas as to the reasons for this effect are discussed.